2017
DOI: 10.1021/acssuschemeng.7b02666
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Thermochemical Process for Adding Value to Used Railroad Wood Ties and Reducing Environmental Impacts

Abstract: A two-step thermochemical process combining a thermal desorption at 250–300 °C and a pyrolysis at 500 °C of used creosote-treated wooden railroad ties was carried out to recover preservative and produce a high quality bio-oil and biochar. Under optimal temperature between 280 and 300 °C, high preservative removal efficiency (70–74%) was achieved with a high proportion of polycyclic aromatic hydrocarbons (PAHs, 80–82%) and a large portion of the original wood mass (67–70%) was retained. This thermally treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Over the years, various investigators have explored pyrolysis as an approach to valorize used railroad ties . We We reported recently on a two‐step thermochemical process that includes the extraction and recovery of preservatives followed by conversion of the thermally treated ties through pyrolysis . This approach recovers a high yield of preservatives with a high level of purity and permits the production of high quality bio‐oil with low amounts of water and acidic compounds and high lignin‐derived bio‐oil.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the years, various investigators have explored pyrolysis as an approach to valorize used railroad ties . We We reported recently on a two‐step thermochemical process that includes the extraction and recovery of preservatives followed by conversion of the thermally treated ties through pyrolysis . This approach recovers a high yield of preservatives with a high level of purity and permits the production of high quality bio‐oil with low amounts of water and acidic compounds and high lignin‐derived bio‐oil.…”
Section: Introductionmentioning
confidence: 99%
“…This approach recovers a high yield of preservatives with a high level of purity and permits the production of high quality bio‐oil with low amounts of water and acidic compounds and high lignin‐derived bio‐oil. The threshold of toxicity for the recovered preservatives is similar to that of a conventional creosote sample . The aim of this study is consequently to evaluate the economic improvement potential of the reported two‐step pyrolysis to upgrade used railroad ties by extracting preservative value and, in so doing, to improve feedstock quality prior to thermochemical conversion by pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations